The New Investment Cycle: Current Finance Mechanisms of Power Engineering Development - V. I. Loktionov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides the analysis of current finance mechanisms of developing power systems in the context of acute necessity to start a new investment cycle. It draws a conclusion that state policy in the field of power engineering cannot foster the development of such mechanisms of its financing as state subsidies on purchase and installation of equipment, contracts on buying electricity and power-service contracts. The analysis of extra opportunities of raising investment showed expediency of developing green mechanisms of financing power engineering in Russia and motivating power companies to conduct IPO. The authors put forward recommendations aimed at attaining the acute objective to develop and implement key initiatives promoting the start of a new investment cycle in order to raise funds for modernizing the existing power projects and opening new ones in accordance with higher ecological requirements. For example, to stimulate the growth of Russian companies' IPO and realize the investment potential of the Russian stock market the Central Bank of the Russian Federation and the Ministry of Economic Development study the possibility to introduce new tax preferences for investors and companies entering the market, which could ensure institutional support for investors and issuers.